Ảnh hưởng của đặc điểm bán hàng hợp kênh đến trải nghiệm người tiêu dùng và ý định mua hàng lặp lại - Trần Thanh , Khiết; Lê Thu , Hà; Nguyễn Thành , Đạt; Nguyễn Hữu , Khôi (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
The role of omnichannel characteristics in fostering positive outcomes has not been clearly established. This study, therefore, proposes and tests a model linking six omnichannel retailing characteristics to repurchase intention through convenient and seamless experiences. To test the hypotheses, the partial least squares structural equation modeling approach was used on a sample of 570 omnichannel consumers. The results reveal that omnichannel characteristics significantly influence convenient and seamless experiences, which in turn promotes repurchase intention. Based on these findings, several theoretical and managerial implications are proposed